RoboCup 2007: Robot Soccer World Cup XI - Visser, Ubbo; Ribeiro, Fernando; Ohashi, Takeshi; Dellaert, Frank (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the proceedings of the 11th RoboCup International Symposium, held in Atlanta, GA, USA, in July 2007, immediately after the 2007 RoboCupSoccer, RoboCupRescue and RoboCupJunior competitions. Papers presented at the symposium focused on topics related to these three events and to artificial intelligence and robotics in general. The 18 revised full papers and 42 revised poster papers included in the book were selected from 133 submissions. Each paper was reviewed by at least three program committee members. The program committee also nominated two papers for the Best Paper and Best Student Paper awards, respectively. The book provides a valuable source of reference and inspiration for R&D professionals and educationalists active or interested in robotics and artificial intelligence.